APLIKASI MUSIK EDITOR GAMELAN RINDIK DENGAN NOTASI BALI BERBASIS ANDROID - I Gede Putra Mas Yusadara; I Gede Harsemadi; Ricky Aurelius Nurtanto Diaz (Jurnal Teknologi Informasi dan Komputer, 2022)
ABSTRACTGamelan Rindik is one of the traditional Balinese gamelan musical instruments consisting of 3 instrumental instruments, namely; plain rindik, sangsih rindik, and 1 distilled piece. People in general find it difficult to have a set of balinese gamelan and are less familiar with balinese notation in a gamelan. Then a music editor application is needed for the gamelan rindik instrument which is used for the process of introducing the gamelan rindik along with balinese notation. The design method is through collecting data from balinese notation literature, Unifieded Modeling Language (UML) and subsequently implementing it. While the purpose and benefits of this application are to produce a rindik gamelan editor music application that makes it easier for parties who are interested in playing rindik gamelan to learn to play rindik without having to buy a set of rindik gamelan. The results of this application can also help in preserving Balinese cultural arts, especially balinese rindik gambelan instruments and Balinese notation produced when playing the application, providing notation output in the form of softcopy and hardcopy as well as rindik sound output from the notation made. The app focuses on creating notations based on the rules of one beat and half beat on universal music.Keywords: music editor, gamelan, rindik, one beat, half a beat.ABSTRAKGamelan Rindik merupakan salah satu alat musik gamelan tradisional bali yag terdiri dari 3 alat instrumental yakni ; rindik polos, rindik sangsih, dan 1 buah suling. Masyarakat pada umumnya kesulitan untuk memiliki seperangkat gamelan bali dan kurang mengenal notasi bali pada sebuah gamelan. Maka diperlukan sebuah aplikasi music editor instrument gamelan rindik yang digunakan untuk proses pengenalan gamelan rindik beserta notasi bali. Metode perancangan melalui poengumpulan data dari literatur notasi bali, Unifieded Modeling Language (UML) dan selanjutnya mengimplementasikannya. Sedangkan tujuan dan manfaat dari aplikasi ini yaitu menghasilkan aplikasi musik editor gamelan rindik yang memudahkan bagi pihak yang tertarik dalam memainkan gamelan rindik dapat belajar bermain rindik tanpa harus membeli seperangkat gamelan rindik. Hasil dari aplikasi ini juga dapat membantu dalam melestarikan seni budaya bali khususnya instrumen gambelan rindik Bali dan notasi Bali yang dihasilkan saat memainkan aplikasi, memberikan output notasi berupa softcopy dan hardcopy serta output suara rindik dari notasi yang dibuat. Aplikasi ini memfokuskan pada pembuatan notasi berdasarkan aturan-aturan ketukan satu dan ketukan setengah pada music universal.Kata Kunci : musik editor, gamelan, rindik, satu ketukan, setengah ketukan